Chick Embryo: A Preclinical Model for Understanding Ischemia-Reperfusion Mechanism - Fauzia, Eram; Barbhuyan, Tarun Kumar; Shrivastava, Amit Kumar; Kumar, Manish; Garg, Paarth; Khan, Mohsin Ali; Robertson, Avril A. B.; Raza, Syed Shadab (Frontiers in Pharmacology, 2018)
Ischemia–reperfusion (I/R)-related disorders, such as stroke, myocardial infarction, and peripheral vascular disease, areamongst the most frequent causes of disease and death. Tissue injury or death may result from the initial ischemic insult, primarily determined by the magnitude and duration of the interruption in blood supplyand then by the subsequent reperfusion-induced damage.Various in vitro and in vivo models are currently available to study I/R mechanism in the brain and other tissues. However, thus far, no in ovo I/R model has been reportedfor understandingthe I/R mechanisms and for faster drug screening. Here, we developed an in ovo Hook model of I/R by occluding and releasing the right vitelline artery of a chick embryo at 72 hours of development. To validate the model and elucidate various underlying survival and death mechanisms, we employed imaging (Doppler bloodflow imaging), biochemical, and blotting techniquesand evaluated the cell death mechanism: autophagyand inflammation caused by I/R. In conclusion, the present model is usefulin parallel with established in vitro and in vivoI/R models to understandthe mechanisms of I/R development and its treatment.